SARS-CoV-2 Infection and Risk Stratification among Healthcare Workers in the Largest COVID-19 Dedicated Tertiary Care Hospital in Dhaka, Bangladesh (Journal of Medicine, 2022)
Background: The health care workers’(HCWs) are working 24/7 in managing devastating pandemicCorona virus disease19(COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARSCoV-2) as front liner which leads them to be at highest risk for contacting infection. In Bangladesh, beinga lower middle-income country and densely populated, the burden is much more on HCWs.Methods: We did a cross-sectional study with an aim to identify the prevalence, risk factors, and outcomesof SARS-CoV-2 infection among the HCWs in a COVID-19 dedicated tertiary care hospital. Statisticalanalysis was done in SPSS version-26. Multivariate regression analysis was done to evaluate risk factorsresponsible for COVID-19 infection and the severity of the COVID-19 disease. We expressed odds ratiowith 95% CI, and considered the p-value of